Condições emocionais de policiais militares do interior de Minas Gerais - SOUSA, Raphaela Campos de (2018)
Research into the health of the military police officer is an important aspect to be understood, especially when considering the fundamental role of this professional within society. Thus, the objective of this dissertation was to verify the prevalence of emotional problems and the level of resilience of military police officers in a city in the interior of Minas Gerais and to investigate their relationships with work characteristics and individual aspects of these professionals. This objective was achieved through three studies, one theoretical and two empirical. The first study was an integrative review aimed at identifying which aspects of the police officers’ mental health have been most investigated in the literature, considering the period from 2012 to 2017. Searches were conducted in the PubMed, Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), and Electronic Periodicals of Psychology (PePSIC). 72 articles were retrieved, which were analyzed in four categories. The analysis of the articles showed the presence of mental illness in police officers of different countries, the main illnesses being depression, stress, post-traumatic stress disorder, and burnout syndrome. For the empirical studies, the Depression, Anxiety and Stress Scale (DASS 21); the Burnout Syndrome Assessment Inventory (ISB); the Resilience Scale; and a sociodemographic and lifestyle questionnaire were used. Study 2 aimed to verify the prevalence of depression, stress, burnout, anxiety and the level of resilience of military police officers in a city in the interior of Minas Gerais. The sample consisted of 148 active police officers and descriptive analysis of absolute and relative frequency distribution, mean, median and standard deviation were performed. The results showed that the majority of the police officers were male (85.10%), married (60.10%), had completed higher education (59.50%), and were, on average, 31.95 years old (SD 6,05). Emotional scales indicated that most police officers had a normal classification for depression (59.90%), anxiety (76.10%), stress (72.50%), Burnout syndrome (80.20%), and 76.70% were resilient. Study 3 aimed to present a measure of emotional illness and to investigate the factors associated with the illness of military police officers. From the initial sample, some participants were excluded, leaving the sample with 128 police officers. Descriptive, bivariate analyzes (Spearman and chi-square correlation) and logistic regression were performed. Those who had severe and extremely severe symptoms of depression or those with moderate to extremely severe levels of depressive symptoms, associated with the presence of burnout, were considered ill. The results identified an illness framework already established in a portion of the military police officers evaluated (14.80%). In addition, they showed that stress, work dissatisfaction and worse perception about mental health were factors associated with the development of illness, while resilience was indicated as a protective factor against illness. The studies showed the importance of investigating the emotional state of the police officers, showing the presence of mental illness in the police officers evaluated, as well as the need for interventions to be implemented within the institution, focusing especially on the development of the professionals’ resilience and their satisfaction with the job.